KNOWING CRITICAL THINGKING IN TWO STRAY LEARNING MODLE - Kanisius Adur (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
This literature study aims to identify the ways of critical thinking with the Two Stray learning model. The data of the study are obtained through collecting literature and conducting a review, collecting relevant study results from 233 articles in the last 10 years on Google Scholar. Then, the researcher compiles the results and discussions, gives conclusions and suggestions. The results of this study show that the Two Stray learning model is able to identify the student’s critical thinking ways; the students play an active role in group discussions, they are able to solve the problems such as assignments given by the teacher, improve their listening skills and critical thinking in the learning process. The students are trained to work together on tasks given by the teacher so that creates effective and fun learning.